(untitled) (Scientific journal of the Fergana State University, 2026)
The article analyzes research dedicated to the life and scholarly activity of the prominent source scholar and orientalist, Academician Buriboy Akhmedov, who played a significant role in the development of Temurid studies in the region. The study seeks to identify the main directions and stages of the scholar’s academic work, as well as his place within historiography.